086 Improving the care of patients with chronic inflammatory rheumatic diseases by including a clinical pharmacist in the multidisciplinary team of a rheumatology department. (23rd September 2015) - Flipon, E; Fonteneau, A; Brazier, M; Fardellone, P
Abstract : Background and Objectives: For optimal self-management of patients suffering from chronic inflammatory rheumatic diseases, a multidisciplinary team should be involved in organising patient follow up and therapeutic education. Our objective was to study the impact of adding a consultation by a clinical pharmacist to the routine physician consultation in our Rheumatology department. Programme: Patients with rheumatoid arthritis or ankylosing spondylitis are offered clinical pharmacy consultations just before they are examined by the rheumatologist. The consultation covers the following: disease duration, drugs taken, satisfaction with current treatment and estimated compliance with treatment. The pharmacist is responsible for broaching the subject of therapeutic patient education and makes proposals for the patient to meet other health professionals. The results of the consultation are communicated directly to the rheumatologist. Any treatment modifications (introduction of drugs, discontinuations, switches to other drugs) are the joint decision of the clinical pharmacist and rheumatologist. Patient satisfaction was assessed using a self-administered questionnaire. Results: 303 patients attended a clinical pharmacy consultation. Overall, 65 treatment changes were proposed. These included folic acid supplementation (n=21), adjusting methotrexate dose (n=11), introduction of drugs acting on inflammation (another disease modifying antirheumatic drug (DMARD), glucocorticoids, nonsteroidal antiinflammatory drugs, biologics (n=16), and miscellaneous drugs (n=17). The main intervention was providing advice and information on the following: biologics, glucocorticoids, bisphosphonates, analgesics, pregnancy, vaccination and osteoporosis. There were 14 reports of adverse effects (biologic agents, n=11, DMARDs and other therapeutics, n=3) and 10 pharmacovigilance reports. 118 patients reported satisfaction with the pharmacy consultation. Discussion and Conclusion: Our study has shown that a clinical pharmacist working in collaboration with a rheumatologist within a multidisciplinary team can help improve patient care by reducing risks through treatment adjustment and by providing tailored advice and information. On the whole, patients were satisfied with the consultation. Contexte et objectif: Nous présentons une expérience de conseil et d'éducation thérapeutique au sein d'un service de Rhumatologie grâce à la création d'une consultation pharmaceutique associée à la consultation médicale. L'objectif de cette consultation est l'organisation pluridisciplinaire du suivi et de l'éducation thérapeutique des patients souffrant de rhumatismes inflammatoires chroniques afin d'optimiser la prise en charge. Programme: Les consultations jumelées médecin-pharmacien concernent les malades atteints de polyarthrite rhumatoïde et de spondylarthrite ankylosante. Le temps de la consultation pharmaceutique est couplé à la consultation du rhumatologue. Les domaines considérés par la consultation pharmaceutique comprennent : la durée de la maladie, l'inventaire des traitements reçus, l'évaluation de la satisfaction du patient pour son traitement, l'estimation de l'adhésion du patient à son traitement. De plus, un dialogue structuré à visée éducative s'instaure sur la prise en charge thérapeutique du patient et des propositions d'orientations vers d'autres praticiens de santé sont faites. Un bilan des données recueillies et un transfert des informations sont effectués avec le Rhumatologue avant sa consultation. Résultats: Au total, 303 patients ont bénéficié d'une consultation pharmaceutique. La satisfaction des patients a été évaluée à l'aide d'un auto-questionnaire à plusieurs dimensions. Les modifications thérapeutiques ont été répertoriées par groupes et en nombre d'interventions : Supplémentation en Spéciafoldine® = 21 // Ajustement de la posologie du Méthotrexate = 11 // Prise en charge du rhumatisme inflammatoire (Autres Disease Modifying Antirheumatic Drugs, Anti-inflammatoires non stéroïdiens, Anti-inflammatoires stéroïdiens, Biothérapies) = 16 // Autres classes = 17 Les conseils et informations les plus fréquents ont été répertoriés. Ils concernaient les éléments suivants : biothérapies, corticothérapie, traitements de fond, bisphosphonates, antalgiques, désir de grossesse, vaccination, ostéoporose et maladie rhumatismale. Les effets indésirables ont été recensés : biothérapies = 11 // traitements de fond =3. Les déclarations de Pharmacovigilance : 10 Le resultat de la satisfaction des patients a été évalués (N=118). Discussion-conclusion: Cette première expérience au CHU montre que le pharmacien permet, en collaborant avec le médecin, d'améliorer la prise en charge des patients par une réduction des risques avec une adaptation des traitements et par des conseils à visées éducatives. Les patients jugent cette démarche très satisfaisante.